2010
DOI: 10.1243/14680874jer525
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the influence of multiple gasoline direct injections on macroscopic spray quantities at different boundary conditions by means of visualization techniques

Abstract: The reduction of combustion emissions and fuel consumption can be achieved by controlling the fuel mixture to be burned and therefore the fuel injection. In this study a gasoline direct injection (GDI) piezo hollow cone injector is investigated by visualization measurements. Both single and double injection events are examined in a pressurized chamber. For the single injection, the influence of the ambient temperature and pressure is analysed in detail. For the double injection, the ambient conditions and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…4, the increasing P amb translated into a slight decrease of the slope during the momentum-driven part of the injection process and a decrease of maximum fuel-spray-tip penetration. This spray behavior is in accordance with the results reported by Martin et al [2]. The influence of P amb was twofold.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…4, the increasing P amb translated into a slight decrease of the slope during the momentum-driven part of the injection process and a decrease of maximum fuel-spray-tip penetration. This spray behavior is in accordance with the results reported by Martin et al [2]. The influence of P amb was twofold.…”
Section: Resultssupporting
confidence: 93%
“…They showed that increasing P amb simultaneously reduced the fuel spray penetration and cone diameter. Such observations were also reported by Martin et al [2] with a 95% isooctane/5% n-heptane fuel. They also looked at the effect of the ambient temperature (T amb ) on spray penetration, concluding it was small compared to that of P amb .…”
Section: Introductionsupporting
confidence: 83%
“…The mentioned CC is designed and fabricated to pressurize till 15 bar. As Martin et al [20] and Liu et el. [21] represented, surrounding pressure a ects the spray properties signi cantly, while surrounding temperature does not have any important e ect on them.…”
Section: Experimental Apparatus and Test Proceduresmentioning
confidence: 82%
“…In the single injection experiment the piston was closer to the injector at the same time after the start of injection due to the later start of injection crank angle. Martin et al [41] found that the penetration length of the hollow cone fuel spray from an outward opening piezo injector increased linearly during injection and the penetration rate decrease significantly at the end of injection in pressure chamber measurements at 0.5 [MPa] and 1.0 [MPa]. Based on the shorter duration of fuel spray impingement on the piston crown and the reduction of the penetration length at the cessation of injection it is conjectured that a smaller fuel mass impinged on the piston crown at ∆t SOI = 478 [µs] in the double injection experiment where injection had ceased compared to the single injection experiment where injection continued.…”
Section: Imagingmentioning
confidence: 99%
“…At ∆t SOI = 978 [µs] the fuel spray penentration length was smaller and the spray was wider compared to the first fuel spray at ∆t SOI = 278 [µs]. Martin et al [41] found that the penetration length and maximum width of the hollow cone fuel spray decreased with increasing pressure. During motored conditions the single injection caused the pressure to decrease by 1 [bar] from 19 [bar] due to vaporization of the fuel.…”
Section: Imagingmentioning
confidence: 99%